Relationship between Knowledge, Attitude and Practice of the Use of Face Mask with Acne among Health Workers at General Hospitals in Mataram City, West Nusa Tenggara, Indonesia - Rifdayani, Dinda; Hidajat, Dedianto; Istikharoh, Umu (Althea Medical Journal, 2023)
Background: The World Health Organization (WHO) has declared the coronavirus a global emergency transmitted by droplets. Personal protective equipment (PPE) such as masks can help lower the  viral infection risk. However, prolonged use of PPE can cause skin lesions and aggravate acne. Acne that develops because of the usage of masks is called mask acne (maskne). Knowledge, attitudes, and practices of health workers regarding the use of face masks can help minimize the occurrence of maskne. This study aimed to assess the relationship between knowledge, attitude ,and practices of the use of face masks with  mask acne among health workers in general hospitals in Mataram City, Indonesia.Methods: This study was a cross-sectional analytic observational study involving health workers from type b and c general hospitals in the city of Mataram, specifically the West Nusa Tenggara Provincial Hospital and the Mataram University Hospital. Primary data were collected using a questionnaire consisting of demographic characteristics, knowledge, attitude, and practice of using masks, then analyzed using Lambda test.Results: In total, 104 respondents were included, of whom 39.4% (n=41) had good knowledge, 35.6% (n=37) had a good attitude towards the use of masks, and 25.0% (n=26) had good practice. Interestingly, 42.3% (n=44) had experienced maskne. Lambda test showed that a relationship between knowledge, attitude, and practices towards the usage of masks and the incidence of maskne (p = 0.014; p = 0.000; p = 0.006).Conclusion: There is a relationship between knowledge, attitudes, and practice of health workers regarding the usage of masks with the prevalence of mask acne at the general hospitals type b and c in the Mataram City. This study implies  is that health workers can prevent the occurrence of mask acne, which can make the work of health workers more difficult.